Method for evaluating the adhesive strength of separators

The proposed method efficiently evaluates the adhesion of separators in secondary batteries by using a composite with alternating adhesive surfaces and measuring torque during separation, addressing the inefficiencies of existing methods and enhancing evaluation accuracy and control.

JP7655633B2Active Publication Date: 2025-04-02LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023556839
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-19
Filing Date
2022-11-01
Publication Date
2025-04-02
Estimated Expiration
2042-11-01

AI Technical Summary

Technical Problem

Existing methods for evaluating the adhesion of separators in secondary batteries are time-consuming and inefficient, particularly for high-capacity batteries with low binder content, leading to insufficient adhesion evaluation.

Method used

A method involving the manufacture of an electrode-separator composite with alternating adhesive and non-adhesive surfaces, followed by cutting and attaching measuring rolls to separate the composite and measure the torque generated, allowing for continuous and efficient adhesion evaluation.

Benefits of technology

This method reduces evaluation time, enables continuous adhesion assessment, and improves process control, thereby ensuring more accurate and efficient evaluation of separator adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655633000001
    Figure 0007655633000001
  • Figure 0007655633000002
    Figure 0007655633000002
  • Figure 0007655633000003
    Figure 0007655633000003
Patent Text Reader

Abstract

The present application relates to a method for evaluating the adhesive strength of a separator, the evaluation method including the steps of producing an electrode-separator composite in which an electrode is laminated on at least one side of a separator, the surfaces where the separator and the electrode face each other include adhesive and non-adhesive surfaces of the separator and the electrode, and the adhesive and non-adhesive surfaces are arranged alternately; transporting the electrode-separator composite; cutting the electrode-separator composite in a direction parallel to the transport direction; attaching measuring rolls to both sides of the cut electrode-separator composite; rotating the attached measuring rolls to separate them from each other, thereby separating the electrode-separator composite; and measuring the torque generated by the measuring roll while separating the electrode-separator composite.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2021-0160462, filed with the Korean Intellectual Property Office on November 19, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a method for evaluating the adhesive strength of a separator. [Background technology]

[0003] Demand for secondary batteries for electric vehicles, mobile devices, etc. is expanding rapidly, and there is a growing demand for state diagnosis and quality stability of secondary batteries.

[0004] These secondary batteries can be classified into nickel-cadmium batteries, nickel-metal hydride batteries, nickel-hydrogen batteries, and lithium secondary batteries. Among them, lithium secondary batteries have a higher operating voltage and better energy density per unit weight than nickel-cadmium batteries and nickel-metal hydride batteries, and are mainly used in portable electronic devices and high-power hybrid vehicles.

[0005] In general, a lithium secondary battery includes an electrode assembly including a positive electrode, a negative electrode, and a separator, an electrode tab extending from the electrode assembly, and an electrode lead welded to the electrode tab. The electrode assembly is a power generating element in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween, and is generally manufactured by stacking the negative electrode, separator, and positive electrode in separate processes and then bonding them by simultaneously applying heat and pressure. However, in the case of high-capacity batteries, a separator containing a small amount of binder, i.e., a thin separator with a low binder content, is often used, and when a battery is manufactured in this manner, a problem occurs in that sufficient adhesive strength cannot be secured between the electrode and the separator.

[0006] Therefore, it is important to use a separator with excellent adhesive strength in order to ensure sufficient adhesive strength, and therefore it is important to evaluate the adhesive strength of the separator. Conventionally, as shown in Figure 2, in order to evaluate the adhesive strength of a separator, a method is usually used in which test pieces of the electrode and separator are manufactured by applying heat and pressure, and a peel test is performed on the test pieces to evaluate the adhesive strength.

[0007] Specifically, as shown in FIG. 2, the peel test is performed by laminating a separator 1 and an electrode 2, each having a width of 25 mm and a length of 60 mm, placing them between polyethylene terephthalate (PET) films 3, and pressing them with a heated press to produce an electrode-separator composite in which adhesive force is generated between the separator and the electrode (FIG. 2(a)). A slide glass 6 is attached to the electrode surface of the electrode-separator composite thus produced using a double-sided adhesive tape 5, and a PET film is attached to a partial area of ​​the separator surface of the electrode-separator composite using a single-sided adhesive tape 4 to produce a test specimen (FIG. 2(b)). The test specimen thus produced is attached to a universal material testing machine, and the force required to separate the separator and the electrode is measured (FIG. 2(c)).

[0008] In this case, because the adhesive strength of the separator varies greatly depending on the position, it is necessary to attach PET films to various positions on the separator surface of the electrode-separator composite for evaluation. However, the task of preparing multiple test pieces and measuring each one takes a lot of time. Due to these constraints, there was a problem that the adhesive strength of the separator could not be evaluated sufficiently (sampling inspection).

[0009] Therefore, a new method for evaluating the adhesive strength of a separator that can overcome these problems is needed. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 10-2016-0023072 Summary of the Invention [Problem to be solved by the invention]

[0011] The present application seeks to provide a method for efficiently evaluating the adhesive strength of a separator over a large area. [Means for solving the problem]

[0012] One embodiment of the present invention provides a method for evaluating adhesive strength of a separator, the method including the steps of: manufacturing an electrode-separator composite in which an electrode is laminated on at least one side of a separator, and the surfaces where the separator and the electrode face each other include an adhesive surface and a non-adhesive surface of the separator and the electrode, and the adhesive surfaces and the non-adhesive surfaces are arranged alternately; transporting the electrode-separator composite; cutting the electrode-separator composite in a direction parallel to a transport direction; attaching measuring rolls to both sides of the cut electrode-separator composite, respectively; separating the attached measuring rolls from each other while rotating them, thereby separating the electrode-separator composite; and measuring a torque generated by the measuring rolls while separating the electrode-separator composite. Effect of the Invention

[0013] A method for evaluating the adhesive strength of a separator according to one embodiment of the present application can reduce the time required for evaluation.

[0014] The method for evaluating the adhesive strength of a separator according to one embodiment of the present application makes it possible to continuously evaluate the adhesive strength of a separator, and can reduce the possibility of defects occurring during the process.

[0015] The method for evaluating the adhesive strength of a separator according to one embodiment of the present application can be easily carried out at any time, allowing for efficient process management. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a side view showing one embodiment of a method for evaluating the adhesive strength of a separator according to the present application. [Diagram 2] FIG. 1 is a diagram showing an embodiment of a conventional method for evaluating the adhesive strength of a separator. [Diagram 3] FIG. 2 is a plan view showing a lamination step in the method for evaluating the adhesive strength of a separator according to the present application. [Figure 4] FIG. 2 is a plan view showing a cutting step in the method for evaluating the adhesive strength of a separator according to the present application. [Diagram 5] FIG. 2 is a plan view showing a measurement process of the method for evaluating the adhesive strength of a separator according to the present application. [Figure 6] FIG. 2 is an enlarged view showing a measurement step in one embodiment of the method for evaluating the adhesive strength of a separator according to the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will now be described in detail so as to be easily understood by those skilled in the art to which the present invention pertains, however, the present invention may be embodied in various different forms and should not be construed as being limited to the embodiments set forth herein.

[0018] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, not excluding other components, unless specifically stated to the contrary.

[0019] In this specification, the term "bonding" refers to a method in which the negative electrode, separator, and positive electrode are each produced in a separate process, and then the separator and the negative electrode and / or positive electrode are laminated together while simultaneously applying heat and pressure. This type of "bonding" is also called "lamination."

[0020] In this specification, the "adhesive surface" refers to the portion where the adhesion has been performed, and the "non-adhesive surface" refers to the portion where the adhesion has not been performed.

[0021] In one embodiment of the present invention, there is provided a method for evaluating adhesive strength of a separator, the method including the steps of: manufacturing an electrode-separator composite in which an electrode is laminated on at least one side of a separator, and the surfaces where the separator and the electrode face each other include an adhesive surface and a non-adhesive surface of the separator and the electrode, and the adhesive surfaces and the non-adhesive surfaces are arranged alternately; transporting the electrode-separator composite; cutting the electrode-separator composite in a direction parallel to the transport direction; attaching measuring rolls to both sides of the cut electrode-separator composite, respectively; separating the attached measuring rolls from each other while rotating them, thereby separating the electrode-separator composite; and measuring a torque generated by the measuring rolls while separating the electrode-separator composite.

[0022] In one embodiment of the present invention, an electrode is laminated on at least one side of the separator, and the surfaces where the separator and the electrode face each other include adhesive surfaces and non-adhesive surfaces of the separator and the electrode, and the step of producing an electrode-separator composite in which the adhesive surfaces and non-adhesive surfaces are arranged alternately includes a step of laminating an electrode on at least one side of the separator to produce a laminate, and a step of heating and pressurizing only a partial area of ​​the laminate, and the partial area may correspond to the adhesive surface of the electrode-separator composite.

[0023] That is, the step of heating and pressing only the regions of the laminate corresponding to the bonding surfaces of the electrode-separator composite may be performed so that bonding surfaces are formed at regular intervals.

[0024] In this specification, the term "constant interval" or "constant distance" means that the distances from a specific position to another specific position are different from each other, as well as that the distances are the same from each other.

[0025] In this specification, the term "distance" refers to the shortest length from a specific position to another specific position.

[0026] In one embodiment of the present invention, the distance between the adhesive surfaces may be the same.

[0027] In one embodiment of the invention, the distance between the adhesive surfaces may vary.

[0028] In one embodiment of the present invention, the step of laminating an electrode on at least one surface of the separator to produce a laminate and the step of heating and pressurizing only a partial region of the laminate may be performed simultaneously using a lamination roll including spaced patterns.

[0029] In one embodiment of the present invention, the adhesive surface may be formed in a stripe shape in a direction parallel to the rotation axis of the measuring roll.

[0030] In this specification, the "laminating roll" refers to a device for producing an electrode-separator composite by adhering a separator to at least one surface of an electrode, and an electrode-separator composite can be produced by laminating the separator and electrode and heating and pressurizing them simultaneously while passing through the laminating roll.

[0031] More specifically, the laminating rolls may have a pattern with a fixed interval, and the separator and the electrode may be laminated and heated and pressed simultaneously while passing through the two laminating rolls, thereby bonding the separator and the electrode. At this time, only the area corresponding to the patterned area may be heated and pressed to produce an electrode-separator composite in which the adhesive and non-adhesive surfaces of the separator and the electrode are alternately arranged.

[0032] In relation to this, FIG. 3 shows a top view of the lamination process of the method for evaluating the adhesive strength of a separator according to the present invention, in which a separator 1 and an electrode 2 are supplied between laminating rolls 10 and 11, an electrode is laminated on at least one side of the separator, and heat and pressure are applied to form an electrode-separator composite in which adhesive and non-adhesive surfaces of the separator and electrode are alternately arranged, and adhesive and non-adhesive surfaces can be formed alternately depending on the pattern formed on the laminating roll (adhesive and non-adhesive surfaces and some configurations are not shown).

[0033] Through the above process, the electrode-separator composite may have a configuration in which adhesive and non-adhesive surfaces are alternately arranged and the adhesive surfaces of the separator and electrode are bonded to form stripes in a direction parallel to the rotation axis of the measuring roll, which is defined as a "pattern laminate" in this specification.

[0034] That is, in this specification, the bonding of the separator and the electrode such that their bonding surfaces form a stripe shape in a direction parallel to the rotation axis of the measuring roll can be defined as pattern lamination.

[0035] When an electrode-separator composite is manufactured by the pattern lamination, an electrode-separator composite having a plurality of adhesive surfaces at regular intervals can be manufactured. This has the advantage that the torque measured when a portion where no adhesive force is formed (non-adhesive surface) is separated can be used as the reference for zero point adjustment, and therefore the adhesive force of the separator can be measured at any time.

[0036] In one embodiment of the present invention, the step of heating and pressurizing only a partial region of the laminate is performed at a temperature of 60° C. to 120° C. and 10 kgf / cm 2 ~100kgf / cm 2 Preferably, the temperature is 70°C to 110°C and the pressure is 20 kgf / cm. 2 ~80kgf / cm2 The mixture may be heated and pressed at a pressure of 1000.

[0037] In one embodiment of the present invention, the heating may be carried out at a temperature of 60°C to 120°C, preferably 70°C to 110°C.

[0038] In one embodiment of the present invention, the pressure is 10 kgf / cm 2 ~100kgf / cm 2 , preferably 20kgf / cm 2 ~80kgf / cm 2 The reaction may be carried out at a pressure of 0.5 to 1000 .mu.m.

[0039] When the above temperature and pressure conditions are satisfied, the separator can be prevented from being deformed by heat or pressure, and thus stable adhesion is possible.

[0040] In this specification, the term "measurement roll" refers to a device for applying force to an electrode and a separator separated from an electrode-separator composite, respectively, in order to evaluate the adhesive strength of the separator.

[0041] In an embodiment of the present application, the step of attaching measuring rolls to both sides of the cut electrode-separator composite may include a step of fixing a partial area of ​​both sides of the electrode-separator composite by the measuring rolls, and a step of rotating each of the measuring rolls. In the step of attaching the measuring rolls, the measuring rolls are rotated to further ensure the fixing of the measuring roll and the electrode-separator composite before separating the electrode-separator composite.

[0042] In an embodiment of the present application, the step of rotating the attached measuring rolls and moving them away from each other to separate the electrode-separator composite may mean the step of applying force to the electrode-separator composite by the respective measuring rolls.

[0043] That is, in an embodiment of the present application, the step of applying force to the electrode-separator composite by each of the measuring rolls may include a step of rotating each of the measuring rolls attached to both sides of the electrode-separator composite and separating the measuring rolls attached to both sides of the electrode-separator composite in a direction perpendicular to the transport direction of the electrode-separator composite.

[0044] That is, as shown in (a) of Figure 1, a portion of each surface of the electrode-separator composite is fixed by the measuring roll (a: fixed portion), which is then rotated. After that, the measuring roll is moved away in a direction perpendicular to the transport direction while applying force to the electrode-separator composite to separate it, thereby separating the electrode-separator composite.

[0045] According to an embodiment of the present application, a method for evaluating the adhesive strength of a separator includes rotating two measuring rolls and moving them away from each other to separate an electrode-separator composite, and evaluating the adhesive strength of the separator from the results of measuring the torque generated by the measuring rolls while separating the electrode-separator composite, thereby making it possible to evaluate the adhesive strength of a plurality of separators and reduce process time. In addition, the evaluation can be easily performed at any time, allowing for efficient process management.

[0046] In one embodiment of the present invention, the electrode may be a positive electrode or a negative electrode, preferably a negative electrode.

[0047] In one embodiment of the present invention, the separator may be a safety reinforced separator (SRS) containing a non-aqueous binder on the surface.

[0048] In one embodiment of the present invention, the electrode may be a negative electrode and the separator may be an enhanced safety separator.

[0049] The safety-enhanced separator is a separator in which a surface of the separator is coated with ceramic particles and a polymer binder, and has enhanced durability and heat resistance. The polymer binder may be a non-aqueous binder.

[0050] The positive electrode may be prepared using a positive electrode active material including primary particles of a metal oxide, and the primary particles of the metal oxide may form irregularities on the surface of the positive electrode. In this case, the non-aqueous binder on the surface of the safety-reinforced separator may physically bond with the irregularities formed on the surface of the positive electrode, thereby achieving high adhesion between the positive electrode and the separator.

[0051] In contrast, since the negative electrode is manufactured using a negative electrode active material containing carbon, irregularities are relatively unlikely to form on the surface of the negative electrode, and therefore the adhesive strength between the positive electrode and the separator is usually stronger than the adhesive strength between the negative electrode and the separator.

[0052] Therefore, evaluation of the adhesive strength of the negative electrode is relatively more important.

[0053] In one embodiment of the present invention, the electrodes may be in the form of electrode sheets. That is, the positive electrode may be a positive electrode sheet, and the negative electrode may be a negative electrode sheet. The electrode sheets may have a specific or fixed size of electrode plate shape by cutting the electrode-separator composite.

[0054] In one embodiment of the present invention, the positive electrode and positive electrode sheet may be manufactured using a positive electrode active material by a method for manufacturing a positive electrode sheet well known in the art, for example, a method in which a positive electrode active material is mixed with a binder or the like to prepare a positive electrode slurry, and the prepared electrode slurry is applied onto a positive electrode current collector, rolled, and dried.

[0055] In this case, the positive electrode active material is not particularly limited as long as it is a material generally used in the field of secondary batteries, and may be, for example, lithium cobalt oxide (LiCoO2), lithium metal oxide (LiMO2) having a layered structure such as a ternary system, spinel-based material (LiM2O4) such as lithium manganese oxide (LiMn2O4), or olivine-based material (LiMPO4) such as lithium iron phosphate (LiFePO4). Aluminum may be used as the positive electrode current collector.

[0056] In one embodiment of the present invention, the negative electrode and the negative electrode sheet may be manufactured using a negative electrode active material by a method for manufacturing a negative electrode sheet well known in the art, for example, a method in which the negative electrode active material is mixed with a binder or the like to prepare a negative electrode slurry, and the prepared electrode slurry is applied onto a negative electrode current collector, rolled, and dried.

[0057] In this case, the negative electrode active material is not particularly limited as long as it is a material commonly used in the negative electrode of secondary batteries in the art, and may be, for example, a carbon (C)-based material, Si, Sn, tin oxide, composite tin alloy, transition metal oxide, lithium metal oxide, etc. Also, the negative electrode current collector may be made of copper or nickel.

[0058] In one embodiment of the present invention, the binder is intended to improve the binding force between the positive electrode active material or the negative electrode active material, and any binder known in the art may be used without limitation. For example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), cellulose, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, EPDM rubber, sulfonated EPDM, or styrene butadiene rubber (SBR) may be used, but is not limited thereto.

[0059] In one embodiment of the present invention, the positive electrode slurry or the negative electrode slurry may further include a conductive material or a filler. The conductive material and the filler may be materials commonly used in the art.

[0060] Specifically, the conductive material may be one or more selected from the group consisting of carbon black such as denka black, acetylene black, ketjen black, furnace black, and thermal black, natural graphite, and artificial graphite, but is not limited thereto. Generally, any material that does not cause a chemical change in the constructed battery and has conductivity can be used.

[0061] The filler may be one or more selected from the group consisting of polyethylene, polypropylene, glass fiber, and carbon fiber, but is not limited thereto. Generally, any fibrous material that does not cause chemical changes in the constructed battery can be used.

[0062] In one embodiment of the present invention, the thickness of the positive electrode is 50 μm to 300 μm, and preferably 100 μm to 200 μm, but is not limited thereto.

[0063] In one embodiment of the present invention, the thickness of the negative electrode is 50 μm to 300 μm, and preferably 100 μm to 200 μm, but is not limited thereto.

[0064] Since the capacity of the negative electrode must be greater than that of the positive electrode, the thickness of the negative electrode is greater than that of the positive electrode.

[0065] In this specification, the thickness of the electrode can be measured by scanning a cross section of the electrode using a scanning electron microscope (hereinafter, SEM) device. In this case, the thickness of the electrode means the thickness including both the electrode current collector and the electrode active material layer.

[0066] In one embodiment of the present invention, the separator may be in the form of a separator sheet. The separator sheet may have a separator shape of a specific or predetermined size by cutting the electrode-separator composite.

[0067] In one embodiment of the present invention, the separator may be a sheet or nonwoven fabric made of an olefin-based polymer, glass fiber, polyethylene, or the like, or kraft paper, and preferably an olefin-based polymer may be used.

[0068] More specifically, one or more materials selected from the group consisting of high density polyethylene, low density polyethylene, linear low density polyethylene, ultra-high molecular weight polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfidro, polyethylene naphthalene, and mixtures thereof may be used, but is not limited thereto.

[0069] In one embodiment of the present invention, the thickness of the separator is 3 μm to 50 μm, and preferably 10 μm to 30 μm, but is not limited thereto.

[0070] In this specification, the thickness of the separator can be measured by scanning a cross section of the separator using an SEM device.

[0071] In one embodiment of the present invention, the step of cutting the electrode-separator composite may be performed using, but is not limited to, a knife, a die, scissors, or a laser.

[0072] In one embodiment of the present invention, the step of cutting the electrode-separator composite may be performed by a cutting roll.

[0073] In relation to this, FIG. 4 shows a top view of the cutting process of the method for evaluating the adhesive strength of a separator according to the present invention, in which a separator 1 and an electrode 2 are supplied between cutting rolls 12 and 13, an electrode is laminated on at least one side of the separator, and heated and pressurized. As the electrode-separator composite in which the adhesive and non-adhesive surfaces of the separator and electrode are alternately arranged is passed, the electrode-separator composite can be cut in a direction parallel to the transport direction (adhesive and non-adhesive surfaces and some components are not shown).

[0074] In one embodiment of the present invention, in the step of cutting the electrode-separator composite in a direction parallel to a transport direction, the distances between the cut portions may be uniform.

[0075] In one embodiment of the present invention, in the step of cutting the electrode-separator composite in a direction parallel to the transport direction, the distance between the cut portions may vary.

[0076] In this specification, the "cutting roll" is a device that cuts the electrode-separator composite.

[0077] In one embodiment of the present invention, the step of transporting the electrode-separator composite may be performed by a conveyor belt, but is not limited thereto, and any means capable of transporting the electrode-separator composite in a certain direction may be used.

[0078] In this specification, the direction in which the electrode-separator composite is transported may be referred to as the "process progress direction". In other words, the step of cutting the electrode-separator composite in a direction parallel to the transport direction means that the step of cutting the electrode-separator composite cuts the electrode-separator composite at regular intervals parallel to the process progress direction (MD). In this way, by cutting at regular intervals and evaluating the adhesive strength, the accuracy of the evaluation can be improved, and by providing a plurality of electrode-separator composites whose adhesive strength can be evaluated, the evaluation time for the adhesive strength can be shortened.

[0079] In one embodiment of the present invention, the step of cutting the electrode-separator composite in a direction parallel to a transport direction may cut the electrode-separator composite at regular intervals.

[0080] In this specification, "cutting the electrode-separator composite at regular intervals" means that the distance between the cut surface of one electrode-separator composite cut parallel to the process direction (MD) and another cut surface has a regular size (or length). Also, "regular size (or length)" means that the deviation of the size (or length) is ±1 mm.

[0081] In this specification, "the step of attaching measuring rolls to both sides of the cut electrode-separator composite" means that the measuring rolls are in contact with both sides of the cut electrode-separator composite so that a constant force can be applied to both sides of the electrode-separator composite.

[0082] In relation to this, FIG. 5 shows a top view of the measurement process of the separator adhesive strength evaluation method according to the present invention, in which measuring rolls 14 and 15 are attached to the electrode-separator composite cut in a direction parallel to the conveying direction by cutting rolls 12 and 13, and the adhesive strength of the separator is evaluated as described below (adhesive and non-adhesive surfaces and some components are not shown).

[0083] In one embodiment of the present invention, the step of measuring the torque generated by the measuring roll while separating the electrode-separator composite may use a torque sensor.

[0084] In one embodiment of the present invention, the step of measuring the torque generated by the measuring roll while separating the electrode-separator composite may include the steps of measuring the torque generated by the measuring roll when the non-adhesive surface of the electrode-separator composite is separated by the measuring roll, determining the torque measured when the non-adhesive surface is separated by the measuring roll as a reference for zero point adjustment, and measuring the torque generated by the measuring roll when the adhesive surface of the electrode-separator composite is separated by the measuring roll. That is, the torque measured when the part (non-adhesive surface) where no adhesive force is formed in the electrode-composite is separated (or separated) is set as zero point, and then the torque measured when the part (adhesive surface) where adhesive force is formed is separated (or separated) is measured, and the adhesive strength of the electrode-separator composite can be expressed as a specific numerical value from the value, thereby enabling the adhesive strength to be evaluated.

[0085] In this specification, the phrase "the electrode-separator composite is separated" more specifically means that the electrode and the separator of the electrode-separator composite are separated from each other, as shown in FIG. 1(a).

[0086] The method for evaluating the adhesive strength of a separator according to an embodiment of the present invention further includes a step of determining the adhesive strength from the measured torque, and the adhesive strength may be calculated according to the following Equation 1:

[0087] [Formula 1]

[0088] S = F / d × sinA

[0089] In the above formula 1,

[0090] S is the adhesive strength of the separator (unit: kgf),

[0091] F is the magnitude of the torque (unit: kgf m) generated by the measuring roll while separating the electrode-separator composite,

[0092] d is the shortest distance between the electrode and the measuring roll rotation axis (unit: m),

[0093] A is the angle (unit: rad) between the electrode-separator composite and the electrode after separation.

[0094] In this specification, the term "the magnitude of the torque generated by the measuring roll while separating the electrode-separator composite" means a value obtained by measuring the torque generated by the measuring roll using a torque sensor or the like. In other words, it means the torque measured by the measuring roll.

[0095] In this specification, sin refers to a trigonometric function, and sinA refers to the sine value of angle A (unit: radian).

[0096] A method for evaluating the adhesive strength of a separator according to one embodiment of the present invention may evaluate the adhesive strength of the electrode-separator composite from the difference between the adhesive strength calculated by the above formula 1 when the non-adhesive surface of the electrode-separator composite is separated by the measurement roll and the adhesive strength calculated by the above formula 1 when the adhesive surface of the electrode-separator composite is separated by the measurement roll.

[0097] The method for evaluating the adhesive strength of a separator according to one embodiment of the present invention may be carried out by a roll-to-roll process, which allows the evaluation of adhesive strength to be carried out in one continuous process.

[0098] Specifically, in the method for evaluating the adhesive strength of a separator according to the present invention, as shown in FIG. 1(b), a lamination process is performed in which a separator 1 and an electrode 2 are supplied between two lamination rolls 10 and 11 on which a certain pattern is formed, an electrode is laminated on at least one side of the separator, and the electrode is heated and pressed to form an electrode-separator composite in which the adhesive and non-adhesive surfaces of the separator and electrode are alternately arranged. In the lamination process, the lamination process and the heating and pressing process are both performed. That is, the electrode-separator composite is manufactured by pattern lamination. Next, the electrode-separator composite manufactured as described above is supplied between cutting rolls 12 and 13, and a cutting process is performed in which the electrode-separator composite is cut at regular intervals based on the process proceeding direction (MD). Measuring rolls 14 and 15 are attached to both sides of the electrode-separator composite cut at regular intervals, and the measuring rolls rotate to fix the electrodes and separators to the measuring rolls. Thereafter, the measuring rolls are rotated and moved away from each other, and a force is applied to both sides of the electrode-separator composite, i.e., the separator and the electrode, respectively, thereby separating the electrode-separator composite, thereby separating the electrode and the separator, and thus separating the electrode-separator composite.

[0099] In this case, the torque measured when the part where no adhesion is formed (non-adhesive surface) is separated (or separated) is set as 0, and then the torque measured when the part where adhesion is formed (adhesive surface) is separated (or separated) is measured to evaluate the adhesive strength of the electrode-separator composite. More specifically, the adhesive strength is evaluated as a value of the difference between the adhesive strength calculated by the formula 1 when the non-adhesive surface of the electrode-separator composite is separated by the measuring roll, and the adhesive strength calculated by the formula 1 when the adhesive surface of the electrode-separator composite is separated by the measuring roll. In this case, the process from deformation by the measuring rolls 14 and 15 to evaluation of the adhesive strength is defined as a measurement process.

[0100] In this case, one or more pairs of cutting rolls 12, 13 and measuring rolls may be used. Taking Fig. 1(b) as an example, the electrode-separator composite is cut at regular intervals by a pair of cutting rolls 12, 13, the electrode-separator composite may be divided into three pieces, and measuring rolls 14, 15 may be attached to each of the electrode-separator composites, so that the adhesive strength may be evaluated. That is, three pairs of measuring rolls (14-1, 15-1, 14-2, 15-2, 14-3, 15-3) may be used.

[0101] In addition, in FIG. 1, ZD corresponds to the thickness direction of the material in the equipment, MD means a direction parallel to the direction of movement of the material in the equipment, i.e., the process proceeding direction, and CD means a direction parallel to the width direction of the material in the equipment and perpendicular to MD.

[0102] Such a process can be performed in one go using a roll-to-roll process as described above.

[0103] 6, in a method for evaluating the adhesive strength of a separator according to one embodiment of the present invention, an electrode 2 is laminated on one side of the separator 1, the surfaces where the separator and the electrode face each other include an adhesive surface and a non-adhesive surface of the separator and the electrode, and when an electrode-separator composite in which the adhesive surfaces and non-adhesive surfaces of the separator 1 and the electrode 2 are alternately arranged is separated by measuring rolls 14 and 15, a torque detected by a torque sensor (not shown) at the measuring roll 15 to which the electrode is attached is recorded in real time. Then, an angle (A) formed between the electrode-separator composite and the electrode after separation is also recorded via a computer vision system (not shown).

[0104] The adhesive strength of the separator can be calculated in real time by substituting the measured value from the above record into the above formula 1. That is, the adhesive strength of the separator can be continuously evaluated at various positions of the electrode-separator composite. As a result, the method for evaluating the adhesive strength of the separator according to the embodiment of the present application can reduce the time required for evaluation, reduce the possibility of defects occurring during the process, and enable efficient process management.

[0105] Although the embodiments of the present invention have been described in detail above, it will be apparent to those having ordinary skill in the art that the scope of the invention is not limited thereto, and that various modifications and variations are possible without departing from the technical idea of ​​the invention described in the claims. [Explanation of symbols]

[0106] 1. Separator 2...electrode 3. PET film 4. Single-sided adhesive tape 5 Double-sided adhesive tape 6. Glass slide 10, 11: Laminate roll 12, 13 Cutting roll 14 (14-1, 14-2, 14-3), 15 (15-1, 15-2, 15-3) Measuring roll a...fixation site

Claims

1. A step of manufacturing an electrode-separator composite in which an electrode is laminated on at least one surface of a separator, the surfaces of the separator and the electrode facing each other include an adhesive surface and a non-adhesive surface of the separator and the electrode, and the adhesive surface and the non-adhesive surface are alternately arranged so that a boundary line between the adhesive surface and the non-adhesive surface is perpendicular to a transport direction; transferring the electrode-separator composite; cutting the electrode-separator composite in a direction parallel to a transport direction; Attaching measuring rolls to both sides of the cut electrode-separator composite, respectively; rotating the attached measuring rolls away from each other to separate the electrode-separator composites; and measuring the torque generated by the measuring roll while separating the electrode-separator composite; A method for evaluating the adhesive strength of a separator, comprising:

2. The step of manufacturing an electrode-separator composite in which an electrode is laminated on at least one surface of the separator, the surfaces of the separator and the electrode facing each other include an adhesive surface and a non-adhesive surface of the separator and the electrode, and the adhesive surfaces and the non-adhesive surfaces are arranged alternately, includes: A step of laminating an electrode on at least one side of a separator to produce a laminate; and applying heat and pressure to only a portion of the laminate; The method for evaluating adhesive strength of a separator according to claim 1 , wherein the partial region corresponds to an adhesive surface of the electrode-separator composite.

3. 3. The method for evaluating the adhesive strength of a separator according to claim 2, wherein the step of manufacturing a laminate by laminating an electrode on at least one surface of the separator and the step of heating and pressurizing only a partial region of the laminate are performed simultaneously using a lamination roll including a spaced pattern.

4. The step of heating and pressing only a partial region of the laminate includes: Temperature of 60°C to 120°C and 10 kgf / cm 2 ~100kgf / cm 2 The method for evaluating adhesive strength of a separator according to claim 2 or 3, wherein heating and pressing are performed at a pressure of .

5. The method for evaluating adhesive strength of a separator according to claim 1 , wherein the adhesive surface is formed in a stripe shape in a direction parallel to the rotation axis of the measuring roll.

6. 4. The method for evaluating adhesive strength of a separator according to claim 1, wherein the step of measuring the torque generated by the measuring roll while separating the electrode-separator composite uses a torque sensor.

7. The step of measuring the torque generated by the measuring roll while separating the electrode-separator composite includes: measuring a torque generated by the measuring roll when the non-adhered surface of the electrode-separator composite is separated by the measuring roll; determining the torque measured when the non-adhesive surface is separated by the measuring roll as a reference for zero point adjustment; and The method for evaluating adhesive strength of a separator according to any one of claims 1 to 3, comprising a step of measuring a torque generated by the measuring roll when the adhesive surface of the electrode-separator composite is separated by the measuring roll.

8. The method further includes determining an adhesive force from the measured torque, The method for evaluating adhesive strength of a separator according to claim 1 , wherein the adhesive strength is calculated by the following formula 1: [Formula 1] S = F / d × sin A In the above formula 1, S is the adhesive strength of the separator (unit: kgf), F is the magnitude of the torque (unit: kgf m) generated by the measuring roll while separating the electrode-separator composite, d is the shortest distance between the electrode and the measuring roll rotation axis (unit: m), A is the angle (unit: rad) between the electrode-separator composite and the electrode after separation.

9. The adhesive force calculated by the formula 1 when the non-adhesive surface of the electrode-separator composite is separated by the measuring roll; The method for evaluating the adhesive strength of a separator according to claim 8, wherein the adhesive strength of the electrode-separator composite is evaluated from the difference between the adhesive strength calculated by the formula 1 when the adhesive surfaces of the electrode-separator composite are separated by a measuring roll.

Citation Information

Patent Citations

  • Continuous measuring device for t-shaped separation strength of laminated body

    JP1992177146A

  • Evaluation method of electrode

    JP2013062139A

  • Device for measuring peel strength of tape

    JP2021148482A

  • Method for manufacturing electrode assembly and electrode assembly manufactured using the same

    KR1020160023072A